Efforts to Increase Students Motivation in Learning History Through Documentary Film Media in Class X SMK Taman Siswa 2 Jakarta - Rosy Pratiwi; Kurniawati Kurniawati (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This article discusses efforts to increase student motivation in history subjects at a vocational high school using a learning medium, namely documentary films. The purpose of this study was to find out the use of documentary films as a learning medium in increasing motivation to study history for class X students majoring in electricity at SMK Taman Siswa 2 Jakarta. This classroom action research took the setting in class X of the Electrical Department of SMK Taman Siswa 2 Jakarta with a total of 35 students. Implementation of activities carried out through 2 cycles. Research data were obtained from observing learning activities, informants (students, teachers, and school principals), documents, and photos of activities with the stages of planning, action, observing, and reflecting. The results showed that there was an increase through the use of Documentary Film media related to student learning motivation in the History subject of class X students in the Electrical Department of SMK Taman Siswa 2. The average student activity reached 70% in cycle 1. In cycle 2 student activity increased by an average 80% in the high category. Students are more active in asking, answering, giving opinions, interacting with groups and collaborating in groups and thinking critically in conveying various arguments regarding various historical events and other social sciences related to these historical events.